2021
DOI: 10.1242/dmm.047357
|View full text |Cite
|
Sign up to set email alerts
|

Selective disruption of trigeminal sensory neurogenesis and differentiation in a mouse model of 22q11.2 deletion syndrome

Abstract: 22q11.2 Deletion Syndrome (22q11DS) is a neurodevelopmental disorder associated with cranial nerve anomalies and disordered oropharyngeal function including pediatric dysphagia. Using the LgDel 22q11DS mouse model, we asked whether sensory neuron differentiation in the trigeminal ganglion (CNgV) , which is essential for normal orofacial function, is disrupted. We did not detect changes in cranial placode cell translocation or neural crest migration at early stages of LgDel CNgV development. As the ganglion coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 88 publications
(157 reference statements)
1
17
0
Order By: Relevance
“…To validate these presumptions, we co-labeled for the transcription factor Six1, which is traditionally used as a marker of placode-derived neurons in the trigeminal ganglion ( Karpinski et al, 2016 ; Karpinski et al, 2022 ; Moody and LaMantia, 2015 ; Motahari et al, 2020 ). At E10.5, we observed that 88.6% of TrkA neurons, 78.0% of TrkB neurons, and 91.8% of TrkC neurons expressed Six1 ( Figure 6A, D, G and J ).…”
Section: Resultsmentioning
confidence: 99%
“…To validate these presumptions, we co-labeled for the transcription factor Six1, which is traditionally used as a marker of placode-derived neurons in the trigeminal ganglion ( Karpinski et al, 2016 ; Karpinski et al, 2022 ; Moody and LaMantia, 2015 ; Motahari et al, 2020 ). At E10.5, we observed that 88.6% of TrkA neurons, 78.0% of TrkB neurons, and 91.8% of TrkC neurons expressed Six1 ( Figure 6A, D, G and J ).…”
Section: Resultsmentioning
confidence: 99%
“…The temporal, regional and lineage-associated diversity of early OE precursors suggests that these cells differ in their proliferative characteristics. We used a pair cell assay (Shen et al, 2002; Tucker et al, 2010; Lehtinen et al, 2011; Karpinski et al, 2021) to distinguish modes of division and fates of isolated E11.5 medial versus lateral OE precursors. A Sox2 eGFP reporter expressed throughout the developing OE but not in the fnm (Ellis et al, 2004; Tucker et al, 2010) identifies presumed neural precursors from the dissected E11.5 medial and lateral OE ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…These distinctions may reflect local signals (see above) that impose positional identity on OE precursor subpopulations. Alternately, they may reflect local cell-cell interactions that nevertheless depend upon the influence of immediate neighbors of similar or distinct identities (Karpinski et al, 2021). Temporal specification of subsets of precursors may provide greater diversity of potential interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways have been discovered to regulate cellular interactions occurring during initial chick trigeminal ganglion coalescence, including Slit1-Robo2, 11,16 Wnt, 39,40 Neuropilin/Semaphorin, 41,42 and various growth factors 43 (e.g., Platelet-Derived Growth Factor 44 ), with many of these also identified in the developing mouse trigeminal ganglion. 45,46 In chick embryos, Robo2 signaling likely modulates levels of N-cadherin post-translationally, but the mechanisms underlying this are still not well characterized. Upstream pathways regulating Cadherin-7 expression in neural crest cells also remain obscure, but it is plausible that the preceding signal transduction pathways could impact the expression of Cadherin-7 and/or N-cadherin during trigeminal gangliogenesis.…”
Section: Discussionmentioning
confidence: 99%